(untitled) (Nepalese Journal of Radiology, 2023)
Most patients with malignant obstructive jaundice present to the hospital in an advanced unresectable stage. Percutaneous transhepatic biliary drainage (PTBD) and stenting are the established , safe and effective way of palliative treatment aiming prolongation and improving the quality of the life. We report a rare case of high output external biliary drainage leading to AKI and electrolyte imbalance following insertion of PTB drain. Patient was managed with hemodialysis and subsequent self- expandable metallic stent (SEMS) placement. We highlight the importance of awareness of this complication and need of further studies regarding role of biliary interventions, associated complications and management.